Radiolabeled Nanogels: From Multimodality Imaging to Combination Therapy of Cancer - Sanchita Ghosh; Weibo Cai; Rubel Chakravarty (Small Science)
Advancements in nanotechnology over the past few decades have offered tremendous possibilities toward cancer theranostics. Radiolabeled nanogels (NGs) represent a promising nanoplatform in this direction, offering a multifunctional toolset for both imaging and therapeutic interventions. This review encapsulates the progressions and potential of radiolabeled NGs in the realm of cancer research. Firstly, multifunctional radiolabeled NGs serve as potent contrast agents for multimodality imaging, enabling precise visualization of tumor sites through various techniques such as positron emission tomography, single‐photon emission computed tomography, optical imaging and magnetic resonance imaging. Furthermore, by incorporating more than one therapeutic payload such as chemotherapeutic drugs, nucleic acids, and/or therapeutic radionuclides, they enable synergistic treatment modalities that address the heterogeneity of cancer cells and their microenvironment. This combination approach allows for enhanced therapeutic efficacy while minimizing systemic toxicity, addressing challenges associated with conventional cancer therapies. Furthermore, the radiolabeling of NGs provides a means for real‐time monitoring of therapeutic distribution and pharmacokinetics, offering valuable insights into treatment response and optimization. Overall, radiolabeled NGs represent a promising platform for the integration of multimodality imaging and combination therapy in the fight against cancer with increased efficacy, reduced toxicity, and improved patient outcomes.